2016
DOI: 10.1177/1541931213601059
|View full text |Cite
|
Sign up to set email alerts
|

Dispatch Decision Making in an Air Medical Transport System

Abstract: Air medical transport relies on effective dispatching of air and land vehicles to provide the fastest and best care possible for patient transfers. These difficult dispatch decisions are characterized by high time pressure, uncertainty, and the dynamic and complex environment of medical transportation. This paper describes a preliminary study of the decision making processes that occur during dispatch decisions at Ornge, the air medical transportation system in Ontario, Canada. We drew upon the Critical Decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…A coordinated system of regional care is essential for providing timely access to treatment for patients who present with a suspected acute stroke. It is estimated that for every minute of delay in treating an ischemic stroke 1.9 million brain cells die, 13.8 billion synapses are damaged, and 12 km of axonal bers are lost [1].Patients who are eligible for time-sensitive therapies should still be transported to the closest hospital capable of providing services for the diagnosis and treatment of stroke [11]. To facilitate transportation in NWO, direct transportation protocols for six regional hospital locations have been established and implemented to support access to care.…”
Section: Stroke Care In Northwestern Ontariomentioning
confidence: 99%
“…A coordinated system of regional care is essential for providing timely access to treatment for patients who present with a suspected acute stroke. It is estimated that for every minute of delay in treating an ischemic stroke 1.9 million brain cells die, 13.8 billion synapses are damaged, and 12 km of axonal bers are lost [1].Patients who are eligible for time-sensitive therapies should still be transported to the closest hospital capable of providing services for the diagnosis and treatment of stroke [11]. To facilitate transportation in NWO, direct transportation protocols for six regional hospital locations have been established and implemented to support access to care.…”
Section: Stroke Care In Northwestern Ontariomentioning
confidence: 99%
“…In this research, we provide a preliminary investigation into the role of individual differences, in particular, the role of numeracy, impulsiveness, and venturesomeness on how operators use a dispatch tool built on historical data to support time estimation. Previously, we found that dispatchers consider a variety of contextual factors when estimating transfer times (Giang, Hui, Donmez, Ahghari, & Macdonald, 2016). We hypothesize that individual differences would influence how operators use contextual information when estimating transfer times using a support tool that displays historical dispatch times.…”
Section: Introductionmentioning
confidence: 99%
“…Medical dispatchers are responsible for the allocation of medical resources in response to incoming patient transfer requests, however, dispatch decision making is a difficult task due to high time pressure and complexity (Wong, Hayes, & Moore, 2005). Dispatch decisions are especially difficult for large-scale air medical transport systems, such as Ornge in Ontario, Canada (Giang, Hui, Donmez, Ahghari, & MacDonald, 2016). Ornge is the sole provider of air medical transport within the province and completes the majority of air and land interfacility transfers using a fleet of fixed and rotary wing aircraft and land ambulances based throughout the province.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations